The Asthma Consultative Process: A Collaborative Approach to Integrating Genomics Into Public Health Practice - Karen L. Edwards, PhD; Tabitha A. Harrison, MPH; Wylie Burke, MD, PhD (Centers for Disease Control and Prevention, 2005)
Genomics research findings on asthma are reported with increasing frequency. As these findings are incorporated into existing knowledge of disease etiology and pathogenesis, the implications for public health practice need to be considered. In 2003, the University of Washington Center for Genomics and Public Health initiated a project to synthesize information about asthma genomics, to examine its relevance to public health research and practice, and to communicate findings to a public health practice audience. This goal was achieved through review of the scientific literature, formation of a working group, and consultations with professionals and community organizations. This paper describes the methods used to conduct these professional and community consultations, referred to as the asthma consultative process, and discusses the lessons learned from this activity.